Pelatihan Penggunaan Platform Merdeka Mengajar bagi Guru SDN Buraen 1 Amarasi Selatan - Yohanes Hariaman Nada; Juliana M. H. Nenohai; Indah Simamora (Universitas Pahlawan Tuanku Tambusai, 2026)
This community service activity aims to address the technical difficulties faced by teachers in using the Merdeka Mengajar Platform (PMM), particularly in understanding the planning features of the Work Plan (RHK), implementing PMM-based learning, and uploading performance achievement documents. This activity is also focused on enhancing teachers' abilities to independently and systematically prepare, implement, and document the Work Plan Results (RHK). The mentoring was conducted for 15 teachers from SDN Buraen 1 Amarasi Selatan, Kupang Regency, East Nusa Tenggara, using an intensive training and mentoring method throughout the odd semester of the 2024/2025 academic year. The results of the activity show that 100% of the teachers successfully completed all RHK assignments in PMM with good and very good ratings. The sustainability of this activity is realised through the formation of an online learning community among teachers so that schools can continue to optimally utilise PMM for the improvement of learning quality in the future.